Promosi Pola Makan Seimbang dalam Meningkatkan Status Gizi dan Pengukuran IMT pada Remaja Putri di Panti Asuhan Fatmawati - Ratih Handayeni; Ayu Widiyanti; M. Amelia Putri Habsari; Leonita Dwi Agustin; Yanti Destriyanti (LPPM Akbid Harapan Ibu Pekalongan, 2026)
Adolescent girls are a vulnerable group to nutritional problems due to physiological, psychological, and behavioral changes related to eating patterns. Imbalanced nutrient intake can negatively affect nutritional status, increase the risk of anemia, disrupt growth and development, and contribute to reproductive health problems. This community service activity aimed to assess the effect of balanced diet promotion on improving knowledge and healthy eating behaviors among adolescent girls, as well as to describe their body mass index (BMI) at the Fatmawati Orphanage, Palembang. The activity was conducted on December 15, 2025, involving 16 adolescent girls. The intervention included nutrition education on balanced diets, demonstrations of healthy menu choices, and practical training on calculating and interpreting BMI. Measurements consisted of body weight, height, BMI, and assessments of participants’ knowledge before and after the counseling session. Data were analyzed and presented descriptively. The results showed that most participants had normal BMI, while a small proportion were underweight or overweight. After the intervention, there was an improvement in knowledge, reflected in understanding of balanced food choices and BMI interpretation. Participants showed positive attitudes toward adopting eating behaviors. In conclusion, balanced diet promotion is effective in increasing knowledge and awareness and supports long-term healthy eating habits.